2016
DOI: 10.12973/eurasia.2016.1210a
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Elementary Teachers’ Beliefs about Nature of Science and Constructivist Teaching in the Content-specific Context

Abstract: The purpose of this study was to explore how Korean preservice elementary teachers' beliefs about nature of science (NOS) and their beliefs about constructivist teaching were structured and related and if any relation was prevalent in the content-specific contexts. As the same format, three versions of questionnaires were developed in three different science content topics, using episodes about rival theories in the history of science and students' relevant alternative conceptions. The data analysis suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The 2 / 12 disciplinary core ideas include physical science, life science, earth and space science, and engineering, which are used to construct explanations and as a form of evidence to support arguments (National Research Council, 2012). Such reforms place high demands on elementary teachers because they play a critical role in early science learning and establishing a scientific foundation for students that can enable or constrain them from continuing their learning experience and achieving the goals of science education reform (Schwarz, 2009;Yoon & Kim, 2016). However, a common challenge for preservice elementary teachers in their future career is their responsibility for teaching the majority of subjects in elementary education.…”
Section: Introductionmentioning
confidence: 99%
“…The 2 / 12 disciplinary core ideas include physical science, life science, earth and space science, and engineering, which are used to construct explanations and as a form of evidence to support arguments (National Research Council, 2012). Such reforms place high demands on elementary teachers because they play a critical role in early science learning and establishing a scientific foundation for students that can enable or constrain them from continuing their learning experience and achieving the goals of science education reform (Schwarz, 2009;Yoon & Kim, 2016). However, a common challenge for preservice elementary teachers in their future career is their responsibility for teaching the majority of subjects in elementary education.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the findings allow prospective teachers a way of shaping their science identity through early inquiry based science practicum teaching to diverse student groups. This finding is in line with previous studies that demonstrated the positive effect of practical experience in classrooms on the views, attitudes, and pedagogical practices of student teachers (Crawford, 2007;Windschitl, 2003;Yoon & Kim, 2016).…”
Section: Collaborative Teaching and Learning Created A Border-crossin...supporting
confidence: 93%
“…Past studies have suggested that teachers’ epistemological beliefs about science play an important role in their teaching practices in the classroom (Hewson and Hewson, 1987; Lederman et al, 2002; Tsai, 2002; Kang and Wallace, 2005), but in our study teachers held similar views on the nature of science, allowing us to consider them equivalent in epistemological beliefs on science, and focus our analysis on the teaching approach only. Teachers might hold sophisticated beliefs about the nature of science, but these do not automatically transfer to their practices (Yoon and Kim, 2016). Moreover, teachers reported similar teaching practices, which are generally associated to general principles of constructivism (use of laboratory, importance of discussion, assigning an active role to students, and the like).…”
Section: Discussionmentioning
confidence: 99%